2018
DOI: 10.1002/jsfa.8937
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of konjac glucomannan/casein blending gels optimized by response surface methodology and assessment of the effects of high‐pressure processing on their gel properties and structure

Abstract: Protein-polysaccharide complexes with excellent properties could be obtained through this method, with broad application prospects in the food industry. © 2018 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Whereas the cooking loss was contrary to the above trend and reached a minimum of 350 MPa. The reason for this change may be due to the fact that the interaction between cowhide collagen and polysaccharides is strengthened with the increase of UHP pressure, the two polymer systems are closer together, and the interactions between non-covalent and hydrogen bonds are significantly enhanced, resulting in a more stable structure of the cowhide gel network [ 31 ]. However, protein denaturation is likely to be induced under excessive pressure, leading to significant disruption of the gel network and a corresponding reduction in the hardness and springiness of the patties [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the cooking loss was contrary to the above trend and reached a minimum of 350 MPa. The reason for this change may be due to the fact that the interaction between cowhide collagen and polysaccharides is strengthened with the increase of UHP pressure, the two polymer systems are closer together, and the interactions between non-covalent and hydrogen bonds are significantly enhanced, resulting in a more stable structure of the cowhide gel network [ 31 ]. However, protein denaturation is likely to be induced under excessive pressure, leading to significant disruption of the gel network and a corresponding reduction in the hardness and springiness of the patties [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have found that with the extension of UHP time, the secondary structure of cowhide collagen changed significantly, the triple helix structure was significantly loosened, and the content of macromolecular components was significantly increased, which enhanced the strength of cowhide collagen gels [ 25 ]. However, when the UHP time is too long, it induces protein deformation, breaks and destroys the gel network structure, and collagen gel strength decreases, leading to a decrease in the hardness and springiness of beef patties [ 31 ]. Combining the four evaluation indexes, UHP times of 15 min, 20 min, and 25 min were selected for response surface optimization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation